HUBUNGAN KEJADIAN IBU HAMIL DIABETES MELLITUS GESTASIONAL DENGAN KEJADIAN PREEKLAMPSIA DI RS BUDI KEMULIAAN TAHUN 2021 - Dyah Marianinngrum; Haivan Kusuma Aji; Annisa Aulia Rahma (Universitas Batam, 2023)
Background: Maternal mortality is still a problem in the world. One of the causes of high AKI is preeclampsia. The increased risk of preeclampsia with the incidence of diabetes mellitus is due to the occurrence of insulin resistance in pregnant women. Women who have preeclampsia are more resistant to insulin after pregnancy. Insulin resistance at 22-26 weeks' gestation is a significant predictor of preeclampsia. Insulin resistance causes impaired glucose tolerance which is a process of diabetes mellitus. Methods: The method in this study was observational analytic, with a case control approach using a purposive sampling technique which was carried out for mothers giving birth at Budi Kemuliaan Hospital in 2021. The sample in this study used the unpaired categorical comparative analytic formula, so that the total sample was 82 people consisting of 41 cases and 41 controls. Data was collected using medical records. Then analyzed using Chi-square. Results: The results based on the Chi Square test showed that there was a significant relationship with p = 0.009 and OR = 5.337. This shows that there is an increased risk of preeclampsia in mothers who have diabetes mellitus. Conclusion: It was concluded that there was a relationship between the incidence of diabetes mellitus and the incidence of preeclampsia in mothers giving birth at Budi Kemuliaan Hospital in 2021.